Customer Brand Loyalty on Apple Products: A Case of Kathmandu Valley - Rana Bhat , Pravesh; Pradhan, Radhe Shyam (Nepalese Journal of Economics, 2025)
This study examines the customer brand loyalty on Apple products: A case of Kathmandu Valley. Customer brand loyalty is the dependent variable. The selected independent variables are product quality, brand image, customer satisfaction, brand trust, and product features. The primary source of data is used to assess the opinions of respondents regarding product quality, brand image, customer satisfaction, brand trust, product features, and customer brand loyalty. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of customer brand loyalty on Apple products: A case of Kathmandu Valley. The study showed a positive impact of product quality on customer brand loyalty. It indicates that satisfactory product quality leads to better customer brand loyalty. Similarly, the study showed a positive impact of brand image on customer brand loyalty. It indicates that a positive brand image improves customer brand loyalty. Likewise, the study also revealed a positive impact of customer satisfaction on customer brand loyalty. It indicates that higher the customer satisfaction, higher would be the customer brand loyalty. Further, the study observed a positive impact of brand trust on customer brand loyalty. It indicates that strong believe towards the products lead to enhances customer brand loyalty. In addition, the study observed a positive impact of product features on customer brand loyalty. It indicates that innovative and attractive product features enhance the customer brand loyalty.